2014
DOI: 10.3844/ajbbsp.2014.40.49
|View full text |Cite
|
Sign up to set email alerts
|

A Short Interfering Rna Molecular Beacon for the Attenuation of Mycobacterial Infection

Abstract: The ability of the pathogen Mycobacterium Tuberculosis (MTB) to invade and survive within macrophages of granulomas is attributed to the product of the Mammalian Cell Entry (MCE) operon whose gene, mce4A, encodes a cholesterol transporter that transports host lipids into the bacterium that allows the bacterium to survive during chronic infection. Here, we proposed and tested the hypothesis that a mce4A siRNA molecular beacon can be used to attenuate mycobacterial infection in macrophages. Mce4A gene was cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…The degree of attenuation of M. smegmatis infection was compared between 3, 6, 24, and 48 h against that at 0 h baseline and was found to be 94.8%, 70.3%, 98.9%, and 93.4%, respectively. Thus, our results showed that the mce4A siRNA was able to significantly attenuate both E. coli-4A and M. smegmatis infection in macrophages [159] . Separate set of experiments were conducted to further test the hypothesis that the mce4A siRNA molecular beacon can attenuate the mce4A mRNA levels in E. coli expressing mce4A gene within infected macrophages.…”
Section: Studies In Our Lab On the Role Of Molecular Beacons In Detec...supporting
confidence: 52%
See 1 more Smart Citation
“…The degree of attenuation of M. smegmatis infection was compared between 3, 6, 24, and 48 h against that at 0 h baseline and was found to be 94.8%, 70.3%, 98.9%, and 93.4%, respectively. Thus, our results showed that the mce4A siRNA was able to significantly attenuate both E. coli-4A and M. smegmatis infection in macrophages [159] . Separate set of experiments were conducted to further test the hypothesis that the mce4A siRNA molecular beacon can attenuate the mce4A mRNA levels in E. coli expressing mce4A gene within infected macrophages.…”
Section: Studies In Our Lab On the Role Of Molecular Beacons In Detec...supporting
confidence: 52%
“…Antisense technology using synthetic siRNAs have been used as a powerful tool in knocking down genes in prokaryotes (and also in eukaryotes), including hepatitis G virus [151] , influenza virus [152] , picornavirus [153] , and Trypanosoma brucei [154] . When targeted to essential genes, siRNAs inhibit growth of E. coli [148,149,155,156] , S. enterica [157] , Staphylococcus aureus [158] , M. smegmatis [159] and MTB [61,160] . Antisense RNAs have been successfully used for the study of bacterial growth and metabolism since this approach allows conditional knock down of target genes [161165] .…”
Section: A Figure 6 Topology Of Typical Atp Binding Cassette Transmem...mentioning
confidence: 99%